2000
DOI: 10.1002/(sici)1438-9312(200003)102:3<218::aid-ejlt218>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soy oil supplementation and protein level in laying hen diets on praecaecal nutrient digestibility, performance, reproductive performance, fatty acid composition of yolk fat, and on other egg quality parameters

Abstract: An experiment was carried out with laying hens in the age of 22—45 weeks to examine the effects of added soy oil (0%, 3.5%, 7%, 10.5%, and 14%) and dietary protein level (13.2% and 16.3%) on laying and reproductive performance, fatty acid composition of yolk fat, and other egg quality parameters. Moreover, digestibility of nutrients and of energy was determined by using a marker technique. Laying intensity and feed intake were not influenced by dietary treatments whereas egg weight and daily egg mass productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…In harmony with the present results, Danicke et al (2000) examined the effects of added soy oil (0, 3.5, 7, 10.5 and 14%) and dietary protein level (13.2 and 16.3%) on precaecal nutrient digestibility in laying hens and found that digestibility of crude protein and amino acids were not affected by either protein content of the diet or by soy oil supplementation. The present results harmonize also with the findings obtained by Han and Thacker (2011), who evaluated the effects of feeding two dietary energy levels (11.81 and 11.39 MJ kgG 1 of ME referred to as high and Table 4: Nutrient digestibility of the experimental diets for 55 weeks old laying hens fed diets containing high nutrient densities Vet.…”
Section: ------------------------------------------------------------supporting
confidence: 78%
“…In harmony with the present results, Danicke et al (2000) examined the effects of added soy oil (0, 3.5, 7, 10.5 and 14%) and dietary protein level (13.2 and 16.3%) on precaecal nutrient digestibility in laying hens and found that digestibility of crude protein and amino acids were not affected by either protein content of the diet or by soy oil supplementation. The present results harmonize also with the findings obtained by Han and Thacker (2011), who evaluated the effects of feeding two dietary energy levels (11.81 and 11.39 MJ kgG 1 of ME referred to as high and Table 4: Nutrient digestibility of the experimental diets for 55 weeks old laying hens fed diets containing high nutrient densities Vet.…”
Section: ------------------------------------------------------------supporting
confidence: 78%
“…This improvement could be attributed to the influence of lecithin as a ready source of phospholipids, choline and essential fatty acids for growth and development of embryos. On the other hand, Danicke et al (2000) reported that level and source of dietary oils did not affect fertilized eggs, hatchability, and mortality of chicks. Data regarding the impact of lecithin on reproductive performance of breeding hens are scarce; however, results with other animal species are promising (Gunther 1996;Dumitru et al 2002).…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, Summers and Leeson (1981) and Donaldson and Ward (1988) found that lecithin had only a positive impact on the absorption of animal fats. Frthermore, Danicke et al (2000) observed that praecaecal crude fat and fatty acids digestibility were non-linearly improved by soybean oil addition. However, CP and amino acids digestibility was not affected by soybean oil, which is similar to the present findings, when no significant effects due to lipid treatments were shown on CP and CF and OM digestibilities (Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of hen diet has an effective factor on egg production (Khajali et al, 2008;Perez-Bonilla et al, 2012), egg weight (Whitehead et al, 1991, Zimmerman 1997Shim et al, 2013) and hatching characters (Danicke et al, 2000) in poultry.…”
Section: Introductionmentioning
confidence: 99%